2014
DOI: 10.14348/molcells.2014.0076
|View full text |Cite
|
Sign up to set email alerts
|

Indacaterol Inhibits Tumor Cell Invasiveness and MMP-9 Expression by Suppressing IKK/NF-κB Activation

Abstract: The β2 adrenergic receptor (ADRB2) is a G protein-coupled transmembrane receptor expressed in the human respiratory tract and widely recognized as a pharmacological target for treatments of asthma and chronic obstructive pulmonary disorder (COPD). Although a number of ADRB2 agonists have been developed for use in asthma therapy, indacaterol is the only ultra-long-acting inhaled β2-agonist (LABA) approved by the FDA for relieving the symptoms in COPD patients.The precise molecular mechanism underlying the pharm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 37 publications
2
17
0
Order By: Relevance
“…NF-κB transcription binding sites located in human MMP-9 promoter region and revealed that NF-κB is the key point in the upregulation of MMP-9 expression ( 64 ). Consistently, previous studies have shown that MMP-9 is a downstream gene in the NF-κB pathway ( 65 , 66 ). Additionally, NF-κB has been reported as a downstream target of IL-17A signaling pathway ( 39 , 40 ).…”
Section: Discussionsupporting
confidence: 88%
“…NF-κB transcription binding sites located in human MMP-9 promoter region and revealed that NF-κB is the key point in the upregulation of MMP-9 expression ( 64 ). Consistently, previous studies have shown that MMP-9 is a downstream gene in the NF-κB pathway ( 65 , 66 ). Additionally, NF-κB has been reported as a downstream target of IL-17A signaling pathway ( 39 , 40 ).…”
Section: Discussionsupporting
confidence: 88%
“…Upon stimulation, this composite is broken down and NF-κB is activated, translocating into the nucleus and controlling transcription of a large number of inflammatory genes (29). As expression of these pro-inflammatory mediators is known to be regulated by NF-κB (30,31), the results of the present study indicated that transcriptional inhibition of these pro-inflammatory mediators by DOME are due to blockage of the NF-κB signaling pathway. In addition, it was demonstrated that translocation of activated NF-κB p65 to the nucleus is significantly inhibited by DOME.…”
Section: Discussionmentioning
confidence: 52%
“…It is known that AP-1 and NF-B transcription factors are important for MMP-9 induction by growth factors, cytokines, and PMA in various cell types (Lee et al, 2014;Lianxu et al, 2006;Shin et al, 2002). We found that galangin and kaempferol drastically decrease IB phosphorylation and increase IB levels.…”
Section: Discussionmentioning
confidence: 67%